THE LABOR OF VISIBILITY: GENDERED SELF-EXPRESSION IN THE SOCIAL MEDIA IMAGINARY - Duffy, Brooke (AoIR Selected Papers of Internet Research, 2015)
From fashion bloggers and beauty vloggers to virtual stylists and digital tastemakers, legions of enterprising young women are flocking to social media platforms with aspirations of capitalizing on their passion projects. Increasingly, their digitally mediated activities entail projections of what Banet-Weiser (2012) has called “the post-feminist self-brand,” which recasts self-expression and mediated visibility as conduits to female empowerment. Despite significant attention to the texts and contexts of gendered self- branding in recent years, further insight is needed to better understand the cultural implications for female social media producers. This paper draws upon in-depth interviews with digital content creators to explore the ambivalences and contradictions inherent in discourses of self-branding, authenticity, and social sharing. After mapping out the role of “ordinary people” in contemporary media culture, I address particular manifestations of “authenticity” and “realness” in the intersecting contexts of post- feminist and digital media milieus. I then present interview data to show how a mode of gendered unpaid work—the labor of visibility—increasingly structures activity in the social media imaginary.